Lipid Profiles and Its Association with Pre-Eclampsia and Eclampsia in Nulliparous Pregnant Women - Asmat Shaheen, Muhammad Waqas Luqman, Syed Fahim Shah, Fozia Zeb, Atta Ullah Khan, Zahoor Ahmed, Asmat Shaheen, Muhammad Waqas Luqman, Syed Fahim Shah, Fozia Zeb, Atta Ullah Khan, Zahoor Ahmed (Journal of Rawalpindi Medical College, 2022)
Objectives: To access the lipid profiles and its association with pre-eclampsia and eclampsia in nulliparous pregnant women. Material and Methods: This cross-sectional study was performed on 234 nulliparous pregnant women with gestation period of > 20 weeks and aged 15-45 years, from March to October 2014, in Institute of Basic Medical Sciences (IBMS), Khyber Medical University (KMU), Peshawar, Pakistan with cooperation from gynecology and obstetrics departments of three tertiary-care hospitals of Peshawar & Khyber Medical College, Peshawar, Khyber Pakhtunkhwa (KP), Pakistan. Subjects were assigned to three groups i.e., group A, group B and group C. For performing biochemical assays and lipid profiling, through ELISA, blood samples were collected from already subjects both with the disease and the controls. Results: Both subjects having pre-eclampsia and eclampsia showed significant elevated levels (p < 0.001) for low density lipoproteins cholesterols (LDL-c), high density lipoprotein cholesterol (HDL-c), total cholesterol (TC)/HDL-c and LDL-c/HDL-c ratio. But TC of pre-eclampsia subjects were found significantly elevated (p < 0.001) in relation to controls. LDL-c/HDL-c and TC/HDL-c also revealed an elevated significant change (p < 0.001) both for pre-eclamptic and eclamptic subjects. On the other hand, only TG/HDL-c in pre-eclamptic patients was found significantly higher (p<0.004) when compared to control group. Conclusion: Serum lipid levels were observed higher in pre-eclampsia and eclampsia patients hence an early assessment is necessary to prevent complications in such patients.